Analisis Sistem Kelistrikan Body pada Sepeda Motor Suzuki Nex-FI - Sotya Anggoro; Zuhri Nurisna; Meilia Safitri; Andhika Wira Pratama (Universitas Muhammadiyah Yogyakarta, 2021)
A motorcycle has an electrical system that functions to make the vehicle operate and provide comfort and safety while driving. Generally, the electrical system on a motorcycle can be divided into three parts: the filling system, the lighting system, and the ignition system. In this study, an analysis was carried out on the body's electrical system, which has more functions in the lighting system. Examining the body's electrical system is carried out by checking the voltage, resistance, and current flowing in each electrical component. The results of these measurements are adjusted to the standard component specifications in the manual. Based on the results of the component inspection, it can be concluded that the inspection of the body's electrical system includes headlights, city lights, rear lights, turn signals, and horns on Nex-FI motorbikes after 5 years of operation in normal conditions according to standards and functions according to their respective roles.